MANAGEMENT OF BUERGER’S DISEASE THROUGH AYURVEDA- A CASE REPORT - Shikha Chaudhary; Divya Kajaria; Rama Kant Yadava (International Journal of Ayurveda and Pharma Research, 2020)
The present case report was about a 50 year-old-male who was diagnosed with Buerger’s disease which is a generalised occlusive vascular diseaseaffecting predominantly males with special predilection to involve the lowerextremities. He presented with complaint of unhealed ulcerations with pain andburning sensation in his right sole for 6 months but not getting satisfactoryrelief even after using conventional medications and advised to get doneamputation. He visited the All India institute of Ayurveda and was treated fortwo months with a combination of Ayurvedic medicines and leech therapy whichshowed significant improvement in patients condition and eventually norecurrence was observed, ulcer healed completely with slight discolouration. Thisshows the effectiveness of Ayurvedic treatment including internal medicinesadministration and leech therapy in preventing amputation and treating othersymptoms which may be useful for clinical practices.